The Emperor’s new NAFTA - Glauber, Joseph W. (University of Guelph, 2019)
On September 30, 2018, the United States and Canada announced they had reached an accord in their renegotiation of the North American Free Trade Agreement (NAFTA). That agreement followed the announcement in August that bilateral negotiations between Mexico and the United States had been concluded. The new treaty, the United States-Mexico-Canada-Agreement (USCMA), if approved by Congress, will replace the 25-year-old NAFTA, an agreement that President Trump had often derided as the “worst trade deal maybe ever signed anywhere.” So, for the U.S. agricultural sector, how does this “wonderful new Trade Deal...a great deal for all three countries” compare to its predecessor, NAFTA? Perhaps the best thing that can be said about the new USCMA is that, effectively, most of the key provisions of NAFTA will remain largely in place. There are changes – some good, some bad – but the USCMA does not change the bulk of the original agreement. That is a good thing, as most farmers and ranchers agree that U.S. agriculture has benefitted significantly under NAFTA.